2020
DOI: 10.21203/rs.2.23323/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LAIR-1 overexpression inhibits epithelial–mesenchymal transition in osteosarcoma via GLUT1-related energy metabolism

Abstract: Background: Leukocyte-associated immunoglobulin-like receptor-1 (LAIR-1) is a collagen receptor belonging to the immunoglobulin superfamily. Although previous studies have evaluated the biological role of LAIR in solid tumors, the precise mechanisms underlying the functions of LAIR-1 as a regulator of tumor biological functions remain unclear.Methods: LAIR-1 expression was evaluated by immunohistochemical analysis using an osteosarcoma (OS) tissue microarray. Wound healing and transwell migration assays were p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…To explore the biological effect of LAIR-1 in vitro, David et al reported that knockdown of LAIR-1 signi cantly inhibited leukemia cell growth and increased apoptosis (Guo et al, 2020). Zhang et al found that LAIR-1 inhibited osteosarcoma cell migration because the overexpression of LAIR-1 dramatically regulated the expression of EMT-related proteins in OS cells through phosphorylating Twist1, a downstream function of Foxo1 (Zhang et al, 2020). Fu et al (Cao et al, 2015) demonstrated that in the cervical cancer cells, overexpression of LAIR-1 inhibited cell proliferation and promoted cell apoptotic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the biological effect of LAIR-1 in vitro, David et al reported that knockdown of LAIR-1 signi cantly inhibited leukemia cell growth and increased apoptosis (Guo et al, 2020). Zhang et al found that LAIR-1 inhibited osteosarcoma cell migration because the overexpression of LAIR-1 dramatically regulated the expression of EMT-related proteins in OS cells through phosphorylating Twist1, a downstream function of Foxo1 (Zhang et al, 2020). Fu et al (Cao et al, 2015) demonstrated that in the cervical cancer cells, overexpression of LAIR-1 inhibited cell proliferation and promoted cell apoptotic capacity.…”
Section: Discussionmentioning
confidence: 99%